Hemoporfin-mediated photodynamic therapy with general anesthesia showed superior efficacy in the treatment of port-wine stains: a retrospective evaluation - Hu, Yan-Yan; Chen, Kai; Wang, Lin-Lin; Wang, Jia-Fang; Chen, Xi; Cao, Li-Juan; Jiang, Qian; Wang, Zhen-Xing; Qian, Shan-Shan; Chen, Zhi-Jun; Chen, Liu-Qing; Li, Dong-Sheng (Frontiers in Medicine, 2023)
Background: Hemoporfin-mediated photodynamic therapy (PDT) is an effective treatment for port-wine stains (PWS), and pain is the main adverse effect of this therapy. General anesthesia is commonly used for pain management during PDT, but the effect of general anesthetics on the subsequent treatment efficacy of PDT in PWS has not been reported. Objectives: To assess the use of general anesthesia combined with PDT compared with PDT alone in 207 PWS patients, and to provide further safety and efficacy data on this combined therapy. Methods: Propensity score matching (PSM) was used at a 2:1 ratio to create a general anesthetic group (n=138) and a highly comparable nonanesthetic group (n=69). The clinical outcomes were evaluated, and the treatment reactions and adverse effects were recorded after one treatment with PDT. Results: After matching, there was no significant difference in the demographic data of the patients in the two groups (p>0.05), while the treatment efficacy was significantly higher in the general anesthetic group than in the nonanesthetic group (76.81% vs. 56.52%, p<0.05). Moreover, logistic regression analysis confirmed that patients receiving general anesthesia showed an association with a good response to PDT (OR = 3.06; 95% CI, 1.57-6.00; p=0.0011). Purpura lasted longer in the general anesthetic group, but the other treatment reactions and adverse effects were similar in the two groups (p>0.05). No serious systemic adverse reactions were observed. Conclusions: We recommend this combined therapy, which is associated with painless, as a high efficacy treatment option for PWS patients, especially for patients with a poor response to multiple PDT alone treatments.